PENGGARAPAN BENTUK PERTUNJUKAN RONTEG SINGO ULUNG DI PADEPOKAN SENI GEMA BUANA PRAJEKAN KIDUL, KABUPATEN BONDOWOSO - Euis Mirna Nurchahya (Institut Seni Indonesia Surakarta, 2015)
This research uses a qualitative method with an interpretative descriptive form whichpresents a picture, description, and explanation of the data obtained from observation and interviews. The results of the data are then presented and explained accordingly. The performance ofRonteg Singo Ulung was created in 1990 and obtained its copyright in 2004. It has earned anumber of rewards and has also become an icon of the Bondowoso district. The goal of this researchis to discover how the performance of Ronteg Singo Ulung was created and how its differentelements are treated, including the background to its creation, its creator, its motivating factors,its artistic interpretation, and its proponents. The method used for collecting data included alibrary study, together with observation, and interviews.Keywords: Form of Ronteg Singo Ulung and Interpretation.